PERANCANGAN INFOGRAFIS PANDUAN SIAGA BENCANA GEMPA DAN TSUNAMI PADA MEDIA BOOKLET - ANGGA RAHMADINATA ASPEN, Drs. Syafwan, M.Si., San Ahdi, M.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2017)
West Sumatra, especially Padang city have potential of natural disaster such as earthquake, lanslide, flood, and so on. The potentially natural disaster occur in Padang is earthquake, which is the geographic state of Padang is closer to Indo-Australia part that potentially cause a huge earthquake (megathrush) and Tsunami. The causes of Padang is in danger zone earthquake , the writer create an infographic media of guidance for earthquake and Tsunami alert which has informative and communicative booklet. The planning method that is used is collecting data trough observation, interview, and documentation. Then it continued with data analysis 5W 1H method. The purpose of this design is designing an informative and communicative booklet for audience target, especially for student and Padang society. This design has the main media as booklet and the supporting media such as banner, poster, x-banner, flyer, calendar, digital booklet, sticker, pin, and T-shirt.Keywords: Booklet, Disaster Alert, Audience.